2011
DOI: 10.1021/ma201088r
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Theories of Rubber Elasticity Using an Ideal Polymer Network

Abstract: Constant amounts of TAPEG and TNPEG (80 mg/mL) were dissolved in phosphate buffer (25 mM, pH 7.4) and phosphate-citric acid buffer (25 mM, pH5.8), respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
118
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 30 publications
9
118
0
Order By: Relevance
“…25 Using FT-IR, p was estimated as the peak intensity ratio of amide to sum of amide and carboxyl groups. 21 Fig . 1 shows the reaction conversion as a function of t deg .…”
Section: B Reaction Conversion Was Tuned By the Pre-dissociation Of mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Using FT-IR, p was estimated as the peak intensity ratio of amide to sum of amide and carboxyl groups. 21 Fig . 1 shows the reaction conversion as a function of t deg .…”
Section: B Reaction Conversion Was Tuned By the Pre-dissociation Of mentioning
confidence: 99%
“…[18][19][20] Although the connectivity and spatial heterogeneities were observed, the degree of heterogeneity was much smaller than that of conventional gels. [21][22][23] In previous studies, we have revealed the requirement conditions for the models predicting G of Tetra-PEG gel, and estimated the credible values of ν and N. [14][15][16][17] Thus, we can calculate and use the values of ν and N from feed condition with no ambiguity.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21] Tetra-PEG gels are formed from mutually reactive tetra-armed PEG prepolymers in an aqueous solution (AB-type crosslink coupling, Figure 1e). The prepolymers have amine and activated ester end groups, resulting in linking through amide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous studies, Tetra-PEG gels at preparation state can be treated as to such ideal networks. [36,37,39] As shown in Figure 3b, when we increased f m from the fully swollen state to the fully deswollen state, the slopes at …”
Section: à2mentioning
confidence: 80%
“…[36] Investigations of infrared spectroscopy and 1 H multiple-quantum nuclear magnetic resonance revealed that the connectivity heterogeneities (unreacted ends and intramolecular links) are highly suppressed compared with conventional rubbery materials. [37,38] The investigation of the small deformation and the fracture test showed that the elasticity of the Tetra-PEG gels simply originates from the chemical crosslinks, and that the contribution of entanglement couplings between network strands is negligible. [39] Based on these results, Tetra-PEG gel is a promising model system as ideal polymer networks.…”
Section: Introductionmentioning
confidence: 99%